Implementasi Kurikulum Berbasis Cinta (KBC) dalam Pembelajaran Bahasa Arab di Madrasah Insan Cendikia - Laili, M Isroul (Konsorsium Dosen Sekolah Tinggi Agama Islam (STAI) Al-Yasini Pasuruan, 2025)
The Love-Based Curriculum is a transformative educational paradigm that centers on instilling values of compassion, empathy, and spirituality throughout the learning process. Rooted in holistic education, this approach seeks not only to develop cognitive abilities but also to foster emotional intelligence and moral integrity. This article explores the practical implementation of a Love-Based Curriculum in the context of Arabic language instruction within madrasas—Islamic educational institutions that inherently balance religious and academic learning.Employing a descriptive qualitative methodology, this study synthesizes insights from recent scholarly literature, policy documents, and educational best practices published over the last five years. The analysis focuses on the strategies teachers use to internalize love-centered principles within their Arabic language teaching. These strategies include the integration of spiritually rich texts, the use of narrative and dialogical pedagogies, and the cultivation of a learning atmosphere characterized by mutual respect and emotional safety. In many cases, Arabic texts are selected or adapted to contain themes of compassion, justice, and humility—reinforcing both linguistic understanding and ethical awareness.The findings reveal that implementing Love-Based principles in Arabic language learning results in several pedagogical benefits. First, students exhibit heightened intrinsic motivation and sustained interest in the subject matter. Second, classroom interactions become more inclusive and empathetic, shifting the teacher-student relationship toward a more nurturing and dialogic model. Lastly, students demonstrate significant development in character-related domains such as cooperation, patience, and ethical decision-making.This study underscores the relevance of moral-emotional frameworks like the Love-Based Curriculum in shaping meaningful and humanistic learning experiences. By integrating values into linguistic instruction, educators can foster not only language proficiency but also nurture compassionate and reflective learners equipped to navigate both academic and social dimensions of life.